Perspectives of nanobiotechnology and biomacromolecules in parkinson's disease. (November 2019) - Adam, Hussaini; Gopinath, Subash C.B.; Arshad, M.K. Md; Adam, Tijjani; Hashim, Uda
Highlights: Parkinson's disease (PD) causes neurological issue, affects central nervous system. PD cause improper regulation in alpha synuclein/dopamine in brain. Different researchers are under investigation with the involvement of microRNA. We review current states & perspectives on PD, including methods & biomolecules. Essence of this review is, PD requires more investigation to help PD patients. Abstract: The universal burden of Parkinson's disease (PD) has more than doubled over the past generation due to the increasing numbers of elderly individuals, with possible contributions from extended disease duration and environmental factors. PD affects the basal ganglia and the substantia nigra in deep parts of the brain. The nerve cells in the substantia nigra produce the neurotransmitter dopamine, which is responsible for the movement of the body. When PD affects the basal ganglia and the substantia nigra in the brain, there is abnormal neurotransmission in the body, leading to speech impairment, slowness of movement (bradykinesia), balance disorder, postural instability, tremor, and muscle rigidity. Even though the cause of this disease is still unknown, some studies revealed that α-synuclein is a major constituent of Lewy bodies, protein clumps that are the pathological hallmark of PD. Furthermore, different lines of research are under investigation with the involvement of other biological macromolecules, such as microRNA and DNA. Therefore, this paper reviews the current states and perspectives on PD, including its nature, features, and management, and the methods available to predict PD. The essence of this review is that PD requires more investigation and the development of suitable technologies to provide assistance to PD patients to improve their life.